La negociación internacional y el obstáculo epistemológico subyacente en la incorporación del discurso cultural (2019)
Vast academic literature reviewed and commonly referenced deals with international negotiation and culture, as if both concepts were equivalent, whereas sometimes the distinction between “intercultural” and “international” is not even made. By addressing both concepts indistinctively, a growing group of scholars and practitioners have misled culture into the international negotiation domain. The following article intends to identify the “common places” of International Negotiation bibliography, highly regarded by scholars and practitioners, especially in international business and management schools. Unfortunately, none of these two concepts is accurate or comprehensive neither in content nor in nature, since they lack a common ground that could eventually lead to an unbiased, intertwining and holistic General Theory on International Negotiation.